Direct Growth of High-Quality InP Layers on GaAs Substrates by MOCVD - K. F. Yarn; W. C. Chien; C. L. Lin; C. I. Liao (Active and Passive Electronic Components)
In this report, we have overcome the drawback of surface roughness of metamorphic buffer layer by LP-MOCVD technique and have grown InP metamorphic buffer layers with various thickness on misoriented GaAs (1 0 0) substrates with 10 degree towards (1 1 1)A. The grown films are characterized by optical microscopy, atomic force microscopy, secondary ion mass spectrometry, transmission electron microscopy and double-crystal X-ray diffraction. We also analyze the surface morphology, which is dependent on growth temperature, group III and group V partial pressure, growth rate and V/III ratios. A mirror-like, uniform surface and high crystal quality of the metamorphic buffer layer directly grown on a GaAs substrate can be achieved. Finally, to investigate the performance of the metamorphic microwave devices, we also fabricate the InAlAs/InGaAs metamorphic HEMT on GaAs substrates.